ANALISIS GEOMETRIK FASILITAS SISI UDARA BANDAR UDARA INTERNASIONAL LOMBOK (BIL) NUSA TENGGARA BARAT - Muttaqin, Aulia; Sartono, Wardhani; Christady, Hary (Civil Engineering Forum Teknik Sipil, 2009)
The economic growth and local advancement require increasing development of local infrastructure, including the air transportation. Selaparang airport in the Province of West Nusa Tenggara apparently has technical limitations for airside and landside development. Therefore, the local government and PT. Angkasa Pura I have formulated a policy to relocate a new airport with international standard, which is to be known as Lombok International Airport (BIL), to replace the Selaparang airport. Data used for the airport reconstruction analysis consisted of technical facilities required for the airside such as runway, taxiway and apron. The International Coorperation Aviation Organization (ICAO) and Federal Aviation Association (FAA) method were used reffering to Boeing Characteristic Airplane and the apron formulation capacity at peak time based on Japan International Coorperation Agency (JICA). Results of the analysis showed that the the reconstruction Phase I and Phase II of planned Lombok International Airport were classified as 4C and 4E, with 11 and 31 runways, respectively based on the ICAO standard by 2028. These figures were in accordance to the results of windrose analysis on system of up to 95% direction site usability factor. The planned airplanes using the airside facilty on Phase I were B 737-400 and MD 82 and B 747-400 on Phase II. The required length for runway of phase I is 3000 m, 4000 m for phase II, and 45 m runway width using the MTOW value. The taxiway dimension analysis was based on ICAO, FAA and Boeing Characteristic Airplane and resulted in 15 m taxiway for phase I and 23 m phase II. The analysis was divided into three analyses. The required apron dimensions for phase I stage 1 (2006, Phase I stage 2 (2016) and Phase II (2028) are 30.000 m2, 44.000 m2, and 123.520 m2, respectively.